Pengaruh Peran Orang Tua dan Lingkungan Sekolah terhadap Hasil Belajar Siswa Pada Mata Pelajaran Dasar Listrik dan Elektronika - Nahydatul Hami; Muldi Yuhendri (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2021)
This study aims to analyze the Study of Effect of the Role of Parents and the School Environment on the Learning Outcomes of Class X Students in Basic Electrical and Electronics Subjects During the Covid-19 Pandemic At SMKN 1 Koto XI Tarusan. The type of research that the author does is a type of quantitative research with a causal associative approach. Data collection was carried out using research instruments by providing a questionnaire with a Likert scale. In variable X1 it was found that a total of all nine indicators of the X1 variable with the respondent's level of achievement of 90.8% and it was stated that the role of parents was good, on the X2 variable it was found that all of the six indicators of the role of the school environment resulted in an accumulation of an average score of 2.87 with the respondent's level of achievement ( TCR) of 114.69%, it can be concluded that the role of the school environment is said to be good and can still be improved. Hypothesis testing was carried out by using multiple linear regression tests T-test (t-test) and F-test. T-test was conducted to partially test the effect of the independent variable on the dependent variable. The F test was conducted to test the effect of the independent variable simultaneously on the dependent variable. The results showed that: (1) there is no influence of parents on student learning outcomes; (2) there is no influence of the school environment on student learning outcomes; (3) there is no influence of the role of parents and the school environment simultaneously on the role of parents in Basic Electrical Electronics subject for class X SMKN 1 Koto XI Tarusan.